PERANCANGAN SISTEM INFORMASI PENJUALAN AM DONUTSDENGAN METODE WATERFALL BERBASIS WEBSITE - Muhamad Dian Rahendra (2023)
Technology is currently developing very rapidly, why is that because with technology we can do many things, especially digital technology. Digital technology is technology based on computer electrical signals, the signals are intermittent and use the binary number system. With digital technology, we can develop various things, from economic activities to social activities, which can be done through digital media. Even now, digital media has started to enter into rural areas. One of the technologies that can be used is the website. Therefore I want to develop a sales information system for AM Donuts which is located in a village that is already starting to be aware of technology, namely the Kerek sub-district village. Moreover, due to the COIVD-19 pandemic, sales have decreased and must be increased in order to survive or progress. The application built will be website-based and use the Waterfall method. This website-based sales information system will be able to order and sell AM Donuts. The purpose of this website-based application is to provide convenience to owners in selling their cakes and to provide convenience to users or customers in ordering and purchasing cakes through the website. Especially now that the village where AM Donuts is located has begun to be open to technology.